APPLYING CRITICAL RACE THEORY TO RACIALLY-MIXED ASIAN-AMERICANS DEPICTED IN KEVIN KWAN’S SEX AND VANITY - Liana, Ni Luh Ayu; Adhitya, Galant Nanta; Kristiawan, Yohanes Angie (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
Michele Yeoh, being the first Asian actress to win an Oscar, might be taken as the model minority, despite Asian immigrants receiving inhumane treatment suspending them from citizenship. Marriage was encouraged to be a US citizen, giving birth to Eurasian children, who can be confused by their parents’ racial differences. They neither have a connection to their parents nor acceptance from either of their parents’ races. This in-between dynamic is explored in Kwan’s Sex and Vanity through Lucie Churchill, whose mother is Asian and father was white. Her life is filled with biracial discrimination. This article was researched by applying four theories: Post-nationalist American Studies; Critical Race Theory; Blank, Dabady and Citro’s discrimination types; and Aguirre and Turner’s reaction types. The findings show that most discrimination types are subtle, unconscious, automatic discrimination, and most reaction types are spontaneous ones. The discrimination and reactions are less vulgar because the upper class apprehends racism in the forms of intentional, explicit discrimination, e.g., physical attack and extermination, are unforgivable. The conclusion drawn is that nonextreme forms still damage mixed-race individuals. This article then argues that identity construction crisscrosses how one identifies himself or herself and how others identify him or her.